Sounds of Silence: Everyday Strategies of Social Repair in Timor-Leste. Issue 1 (2nd January 2016) - Kent, Lia
Abstract: Transitional justice discourse and practice is imbued with assumptions about the liberatory power of speech, and constructs silence as a marker of absence, pathology or continuing repression. This article unsettles these assumptions by examining some of the 'everyday' ways in which East Timorese people are seeking to rebuild their lives in the aftermath of the Indonesian occupation. Close attention to everyday strategies and practices of social repair brings to the fore the 'civil' and 'pragmatic' dimensions of silence, while also underscoring the significance of relational and embodied forms of communication in the Timor-Leste context. I conclude that, rather than viewing silence as a 'problem', more attention should be paid to its diverse meanings, and to the rich realm of everyday life in which they are embedded.